MANAJEMEN BALANCED SCORECARD KINERJA GURU DI MI MUHAMMADIYAH KECAMATAN PANDANARUM BANJARNEGARA DALAM MENINGKATKAN PRESTASI MADRASAH - Sudadi, Sudadi; Widiyanto, Teguh Heru (Jurnal Ilmiah Citra Ilmu, 2022)
This thesis examines the management of the Balanced Scorecard of Teacher Performance at MI Muhammadiyah , Pandanarum District, Banjarnegara Regency in Improving Madrasah Achievement. The results of the study found that: 1) The performance of teachers in the customer perspective is in the very good category because the teacher's performance is in accordance with the expectations of education customers which have an impact on increasing customer satisfaction of the madrasah education; 2) Teacher performance from a financial perspective is in the poor category, because the teacher's performance is not comparable to the results obtained in the form of salaries and subsidies provided by madrasah; 3) The performance of teachers at MI Muhammadiyah , Pandanarum District, Banjarnegara Regency in the perspective of internal processes is said to be good, this is evidenced by teacher innovations in improving learning and educational service processes and 4) Teacher performance at MI Muhammadiyah NU 1, Pandanarum District, Banjarnegara Regency, from the perspective of learning and growth, is said to be good. This is evidenced by looking at several indicators which include: improvement of quality and competence (quality of human resources), personality development and increased teacher satisfaction.